Comparative characterization of botulinum neurotoxin subtypes F1 and F7 featuring differential substrate recognition and cleavage mechanisms. (1st March 2016) - Guo, Jiubiao; Chan, Edward Wai Chi; Chen, Sheng
Abstract: BoNT/F7, one of the seven subtypes of botulinum neurotoxin type F (F1 to F7), is the second-most divergent subtype of this group. Despite sharing >60% identity with BoNT/F1 at both holotoxin and enzymatic domain levels, it requires an N-terminal extended peptide substrate for efficient substrate cleavage, suggesting its unique substrate recognition and specificity mechanism. Substrate mapping and saturation mutagenesis analysis revealed that VAMP2 (20–65) was likely a minimally effective substrate for LC/F7 (light chain of BoNT/F7), and in addition, LC/F7 recognized VAMP2 in a unique way, which differed significantly from that of LC/F1, although both of them share similar substrate binding and hydrolysis mode. LC/F7 utilizes distinct pockets for specific substrate binding and recognition in particular for the B1, B2 and S2 sites recognitions. Our findings provide insights into the distinct substrate recognition features of BoNT subtypes and useful information for therapy development for BoNT/F. Highlights: BoNT/F7 is the second-most divergent subtype among BoNT/F. LC/F7 recognized VAMP2 in a unique way compared to LC/F1. Minimal substrate for LC/F7 is VAMP2 (20–65). The most significant difference between LC/F7 and/LC/F1 is their substrate binding and recognition at B1, B2 and S2 sites. Our findings provide insights into the distinct substrate recognition features of BoNT subtypes.